Counseling On Prevention Of Scabies Transmission, Scabies Screening And Secondary Infection Through Gram Examination And Comprehensive Scabies Treatment - Sukmawati Tansil Tan; Yohanes Firmansyah; Alicia Sarijuwita; Joshua Kurniawan; William Gilbert Setyanegara (Pusat Riset dan Inovasi Nasional, 2023)
Scabies is a highly contagious infection that falls under the category of neglected diseases. If not treated as soon as possible, scabies rapidly spreads throughout a community, causing significant distress for those affected. In a more advanced stage, scabies can lead to malnutrition in children and threaten their growth and development. Obviously, scabies can impair the quality of life of adult patients. In addition to screening and diagnosis as early as possible to prevent secondary and tertiary infections, education regarding the prevention and complete treatment of scabies is crucial. This community service therefore focuses comprehensively on educating the public about the introduction and prevention of scabies transmission, in addition to screening for scabies by doctors and examination of secondary infections by performing gram examinations, screening for growth disorders caused by scabies, and comprehensive treatment for not only sufferers, but also their families